Stent-assisted treatment of unruptured and ruptured intracranial aneurysms: clinical and angiographic outcome. (October 2013) - Galal, Ahmed; Bahrassa, Farhad; Dalfino, John C.; Boulos, Alan S.
Abstract Background. Wide-necked and non-saccular aneurysms are difficult to treat with coil embolization. The use of stents has expanded the role of endovascular treatment. Methods. A retrospective study of 43 patients with wide-necked, fusiform or blister aneurysms treated with stent-assisted coiling or stent alone. The review of medical files and images allowed retrieval of the following patient characteristics: (1) age and gender; (2) aneurysm characteristics (site, size, status (ruptured versus unruptured)); (3) coils used; (4) type of stent; (5) complications (procedural and delayed); (6) degree of aneurysm occlusion; (7) length of follow-up; and (8) clinical outcome (modified Rankin scale). Results. Most of the aneurysms treated were located in the anterior circulation (60.4%), while posterior circulation aneurysms represented 39.5%. There are 38 (88%) saccular aneurysms, 1 (2%) fusiform aneurysm and 4 (9%) blister aneurysms. Unruptured aneurysms represented 65%, while ruptured aneurysms represented 35%, 21% of which were treated with a stent in the acute stage. Stent-coiling was performed in 90.7% of cases. Stent alone was performed in 9.3% of cases. The overall radiographic complication rate was 11.6%. Clinically manifest procedure-related complication rate was 4.7%. A complete or near complete (residual neck) embolization was achieved initially in 60.4% of cases. Of the 28 patients with a mean follow-up of 20 months, 57.1% showed a complete occlusion and 25% showed a remnant neck on follow-up. Conclusion. Stenting facilitates the treatment of wide-necked, fusiform or blister aneurysms. There is an increased rate of delayed aneurysmal occlusion with subsequent follow-up. A significantly higher rate of occlusion was also observed in the subgroup of aneurysms coiled by a combination of hydrocoils and bare platinum coils versus bare platinum coils only. Stents may also be used in the acute phase of ruptured aneurysms in carefully selected patients.